Is normal β-hCG regression curve helpful in the diagnosis of persistent trophoblastic disease?. Issue 5 (1st August 2004) - Behtash, N.; Ghaemmaghami, F.; Honar, H.; Riazi, K.; Nori, A.; Modares, M.; Mousavi, A.
Abstract : Objective: The aim of this study was to evaluate the probable usefulness of normal β-human chorionic gonadotropin (β-hCG) regression curve in the diagnosis of persistent trophoblastic disease (PTD). Methods: A log-value regression curve was developed from the means and 95% confidence limits of serial weekly serum β-hCG titers of 43 patients with uneventful complete hydatidiform moles and 14 patients, who were previously confirmed as PTD. Results: All 14 PTD patients (100%) had abnormal values, beyond normal range, within 4 weeks. β-hCG was in its upper values, compared to normal regression curve at 2.29 ± 0.19 weeks. This was earlier than plateau or rise detection at 4.21 ± 0.33 weeks ( P < 0.001). Within 3 weeks of evacuation, 13 of 14 (92.86%) PTD patients' β-hCG values exceeded the normal range, whereas only six of 14 (42%) showed a rise or plateau. Conclusion: Our finding indicates that the normal β-hCG regression curve may be useful for quicker detection of PTD than the plateau or rise of level.